(untitled) (American Journal of Business Management, Economics and Banking, 2022)
Most countries indiscriminately view investment as an imperative and a necessary tool for economic growth and effective management to promote the economy. After 2003, the Iraqi economy entered a new phase represented by the trend towards the application of a free market economy and support for the private sector. Accordingly, the Iraqi state has enacted a number of investment promotion laws, perhaps the most prominent of which is Investment Law no. 13 (2006) and its subsequent amendments for providing an appropriate and attractive environment for foreign investment within the framework of economy and its variables. Since investment of both types has clear effects on the level of its economic variables, this research aims at investigating the existence of a long-term balance among interest rates, investment expenditure and foreign direct investment (FDI), building the measurement model and verifying its quality, in addition to discovering and addressing the problems. The results revealed a long-term balance between the research variables, and the degree of adjusted r-squared coefficient was good represented by (73%). The measurement results indicated the lack of problems related to the model.